Kewenangan Notaris Membuat Surat Keterangan Waris Sebagai Tanda Bukti Ahli Waris - Agustiningrum, Nanik; Widhiyanti, Hanif Nur; Sri Kawuryan, Endang (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 1 (2025)DO - 10.24843/JMHU.2025.v14.i01.p12, 2025)
This study aims to examine in depth the authority of notaries to make a Certificate of Inheritance Rights Article 111 paragraph (1) letter c number 5 of the Regulation of the Minister of ATR/Head of BPN Number 16 of 2021 in relation to the provisions of the Notary Position Law. This study uses a normative legal method with a statutory and conceptual approach to analyze the inconsistencies in norms that arise after the enactment of the Regulation of the Minister of ATR/BPN 16 of 2021. The results of the study indicate that although the UUJN still grants authority to Notaries in making a Certificate of Inheritance Rights (SKHW), the inconsistency of the wording in the Regulation of the Minister of ATR/BPN 16 of 2021 has the potential to cause differences in interpretation and administrative obstacles in the process of registering inherited land. This inconsistency can weaken legal certainty for heirs and has the potential to cause land disputes. Therefore, harmonization is needed between the Regulation of the Minister of ATR/BPN and the UUJN to ensure that the authority of Notaries in making SKHW remains clearly recognized in the land administration system. In addition, technical guidelines from the National Land Agency (BPN) are needed to avoid implementation obstacles and ensure legal certainty in the registration of inherited land. Studi ini bertujuan untuk mengkaji secara mendalam terkait kewenangan notaris Pembuatan Surat Keterangan Hak Waris Pasal 111 ayat (1) huruf c angka 5 Peraturan Menteri ATR/Kepala BPN Nomor 16 Tahun 2021 dikaitkan dengan ketentuan Undang-Undang Jabatan Notaris. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual guna menganalisis inkonsistensi norma yang timbul pasca-berlakunya Permen ATR/BPN 16 Tahun 2021. Hasil penelitian menunjukkan bahwa meskipun UUJN tetap memberikan kewenangan kepada Notaris dalam pembuatan Surat Keterangan Hak Waris (SKHW), ketidaksesuaian redaksi dalam Permen ATR/BPN 16 Tahun 2021 berpotensi menimbulkan perbedaan tafsir dan kendala administratif dalam proses pendaftaran tanah warisan. Inkonsistensi ini dapat melemahkan kepastian hukum bagi ahli waris dan berpotensi menimbulkan sengketa pertanahan. Oleh karena itu, diperlukan harmonisasi antara Permen ATR/BPN dan UUJN guna memastikan bahwa kewenangan Notaris dalam pembuatan SKHW tetap diakui secara jelas dalam sistem administrasi pertanahan. Selain itu, pedoman teknis dari Badan Pertanahan Nasional (BPN) diperlukan guna menghindari kendala implementasi dan memastikan kepastian hukum dalam pendaftaran tanah warisan.